Global trends and prospects in research of artificial cornea over past 20 years: a bibliometric and visualized analysis - Cai, Youran; Zhou, Jiaxin; Xu, Xuyang; He, Bingbing; Zou, Wenjin (International ophthalmology, 2023)
Background Many studies have been focused on the area of the artificial cornea. In our study, a bibliometric analysis was performed on the artificial cornea to identify the global key research fields and trends over the past 20 years. Methods Publications about artificial cornea were retrieved and downloaded from the Web of Science Core Collection from 2002 to 2021. CiteSpace and VOSviewer were used to analyze countries, institutions, authors, and related research areas. Results A total of 829 eligible publications were analyzed. The USA was the most productive country for the artificial cornea, followed by China and Canada. Harvard University was the most prolific institution in this field. Cornea published most of the studies in this area and Dohlman CH was the most cited author. Conclusions Bibliometric analysis in our study first provides a general perspective on the artificial cornea, which can be helpful to further explore the issues in the rapidly developing area.